Spory o wiersz Josifa Brodskiego На независимость Украины. Część 2 - Fast, Piotr (Przegląd Wschodnioeuropejski, 2026)
The article attempts to reconstruct the premises that led to Joseph Brodsky’s writing of the (anti)elegy On the Independence of Ukraine. According to critics’ opinions that accuse the poet and justify his attitude, Brodsky was influenced by many external factors (e.g., the ideological pressure of the culture in which he was formed) and often unconscious psychological stimuli, which were a realisation of the social unawareness of Russian culture. In the article, opinions of famous intellectuals, writers and literary critics (Czesław Miłosz, Bengt Jangfeld, Oksana Zabużhko, Aleksander Fiut, and others) were taken into account.